New Approach to Planning and Forming of Current Costs for Infrastructure Repairs Based on the Normative Method - D. S. Rubchenko (Вестник Научно-исследовательского института железнодорожного транспорта)
The article presents the relevance of planning and forming enlarged norms of current costs for rail infrastructure repairs and maintenance, differentiated by class of lines and specialization of facilities: track and engineering structure, automatics and telematics, electrification and power supply. Enlarged norms of current costs is planned to be developed in accordance with the classification and specialization of railway lines, as well as with the URRAN methodology which are among the main criteria for the economic feasibility of repair or prolonging the life and selection of projects for funding, with limited resources, to make reasonable decisions when determining volumes of work on the infrastructure facilities. Planning of financial resources to maintain objects of the railway infrastructure is supposed to be performed on the basis of a normative method which is that in case of determination of a limit of company funds the normalized resources are used: material consumption rate, performance and maintenance rate, labor input, standard rates of use of machines and mechanisms, duration of production cycle, etc. There are benefits of planning and forming of current costs for rail infrastructure repairs and maintenance using estimate documentation: a common methodological approach in the preparation of budget documentation for construction, reconstruction, repair and maintenance of infrastructure considering normative indicators based on the optimal work technology and the use of modern machinery; decrease the complexity of calculations, simplifying the definition of planned cost of work and checking of the results; specification, calculation accuracy and the possibility of their control; rail regional features register.